2017
DOI: 10.3164/jcbn.17-41
|View full text |Cite
|
Sign up to set email alerts
|

Epigastric pain syndrome accompanying pancreatic enzyme abnormalities was overlapped with early chronic pancreatitis using endosonography

Abstract: There was not available data about the overlap between functional dyspepsia (FD) and pancreatic diseases. We aimed to determine whether epigastric pain syndrome (EPS) accompanying with pancreatic enzyme abnormalities were associated with early chronic pancreatitis proposed by Japan Pancreas Society (JPS) using endosonography. We enrolled 99 consecutive patients presenting with typical symptoms of FD, including patients with postprandial distress syndrome (PDS) (n = 59), EPS with pancreatic enzyme abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Then, the reason why certain populations of EPS are resistant for the treatment using anti-acid therapy or prokinetics are considered as the involvement with several other overlapped diseases. We have also reported that almost 40% of FD patients with abnormalities of pancreatic enzyme was determined as early chronic pancreatitis (ECP) using endosonography (19). Our results suggest that the measurement of early phase of gastric emptying may be a useful tool to distinguish ECP patients from FD patients.…”
mentioning
confidence: 66%
“…Then, the reason why certain populations of EPS are resistant for the treatment using anti-acid therapy or prokinetics are considered as the involvement with several other overlapped diseases. We have also reported that almost 40% of FD patients with abnormalities of pancreatic enzyme was determined as early chronic pancreatitis (ECP) using endosonography (19). Our results suggest that the measurement of early phase of gastric emptying may be a useful tool to distinguish ECP patients from FD patients.…”
mentioning
confidence: 66%
“…In 2015, in Japan, new guidelines for FD were approved and also described that 24% of FD patients involved had chronic pancreatitis [15,18]. We have reported that 41% of FD patients with abnormalities of pancreatic enzyme were determined as ECP using EUS [19,20]. Ashizawa et al [21] have also reported that anti-acid-therapy-resistant FD involves FD patients concomitant with chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 91%
“…The second approach concerns symptoms and events of acute pancreatitis. Dyspepsia is a common manifestation of pancreatic exocrine dysfunction and can be classified as epigastric pain or postprandial distress syndrome [16, 17, 18]. The confirmation of acute pancreatitis needs clinical, laboratory, and image data, but patients do not always undergo complete examinations.…”
Section: Introductionmentioning
confidence: 99%